Eosinophil-rich trichoblastic carcinoma with aggressive clinical course in a young man - Toberer, Ferdinand; Enk, Alexander; Hartschuh, Wolfgang; Hänßle, Holger (Journal of cutaneous pathology, 2017)
We present the case of a 35-year-old man who developed a follicular differentiated cutaneous carcinoma with an eosinophil-rich infiltrate and an aggressive clinical behavior. After an in-depth histopathological investigation the diagnosis of trichoblastic carcinoma was made. Over the course of the disease the patient developed a cutaneous in-transit metastasis as well as an axillary lymph node metastasis 18 months after the excision of the primary tumor on his back. Based on a literature review we discuss the different concepts behind the term “trichoblastic carcinoma” and we summarize the clinical and histological details of previously reported cases. Furthermore, we focus on the phenomenon of tumor-associated eosinophilia.
First published: 04 September 2017
Gesehen am 25.06.2018